Effect of enzyme supplementation on the digestibility, blood biochemical and performance of crossbred gilts fed diets with increasing levels of rice bran - SOREN, N M; BHAR, R; MANDAL, A B (The Indian Journal of Animal Sciences, 2014)
Influence of increasing levels (0.0–RB 0, 410 g/kg-RB1 and 820 g/kg-RB2) of rice bran (RB) along with or without feed enzyme (E) supplementation was studied for growth, nutrient utilization, blood biochemical and oestrous in crossbred gilts for 112 days. Pigs (54) were randomly divided into 6 groups and each treatment was replicated 3 times and 3 gilts were housed together in a pen to form the experimental unit. The enzyme complex contained cellulase, ß-glucosidase, xylanase, α-amylase and protease. Feed intake, growth rate, feed: gain was similar but decreased due to the increase in dietary level of rice bran in RB2. DM intake, ADG and feed utilization efficiency was similar in the control and 410 g/kg rice bran incorporated diets, while it reduced significantly in RB2 diet in comparison to control. The digestibility of all the nutrients, except ether extract (EE) was reduced as the proportion of RB increased in the diets. The groups fed rice bran at higher level had lower serum glucose level than any other diets. Enzyme addition to RB2 improved blood glucose level than control. Enzyme supplementation decrease the duration of estrous (h) in gilts fed on RB based diets. It was concluded that addition of feed enzymes did not improve the performance of crossbred gilts fed on diets containing higher level of rice bran.